(untitled) (Economic and Political Thought, 2018)
The present paper discusses the following research questions: To what extent did President Kuchma’s mistakes made during his final presidency have impact on Ukraine’s inability to conduct systemic reforms (e.g. combating corruption, development of the foundations for a stable state based on the rule of law with free market economy)?, Can it be stated that the lack of radical reforms and mistakes in Ukraine’s foreign policy during Kuchma’s final presidency contributed to the outbreak of the Orange Revolution, and also enabled Viktor Yanukovych to take leadership and in fact resulted in the Euromaidan? Can the final stage of Kuchma’s presidency (2001–2004), especially in terms of foreign policy, be characterised as multi-directional with the emphasis on the rapprochement with Russia?